Model Suggesting that Replication of Influenza Virus Is Regulated by Stabilization of Replicative Intermediates - Vreede, Frank T. (American Society for Microbiology, 2004)
The RNA-dependent RNA polymerase of influenza A virus is responsible for both transcription and replication of negative-sense viral RNA. It is thought that a “switching” mechanism regulates the transition between these activities. We demonstrate that, in the presence of preexisting viral RNA polymerase and nucleoprotein (NP), influenza A virus synthesizes both mRNA (transcription) and cRNA (replication) early in infection. We suggest that there may be no switch regulating the initiation of RNA synthesis and present a model suggesting that nascent cRNA is degraded by host cell nucleases unless it is stabilized by newly synthesized viral RNA polymerase and NP.